PENGARUH PELATIHAN TERHADAP PEMENUHAN KONTRAK PSIKOLOGIS DIMODERASI OLEH ORIENTASI RELASIONAL INDIVIDU - Vania Talesia; Nang Among Budiadi; Sugiyarmasto . (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the effect of training on psychological contract fulfillment as moderated by the individual's relational orientation. The data were obtained from the questionnaires distributed to employees Jiwa Hospital of Surakarta and PKU Muhammadiyah Hospital of Surakarta. The sampling technique used is cluster sampling with a population of 149 hospital employees. Hypothesis testing is performed using regression analysis using SPSS 18. The results of this study indicate that training has a significant effect on psychological contract fulfillment and relationship orientation moderates the relationship between training and psychological contract fulfillment.